IDENTIFYING BARRIERS TO INTEGRATING BIM TECHNIQUES INTO BUILDING SUSTAINABILITY ASSESSMENT: A HYBRID DELPHI-AHP ANALYSIS - Naji, Alaa Jaleel; Abu Mahadi, Mohamed I.; Al-hchaimi, Muataz Jabbarn Jiheel (Journal of Applied Engineering Science, 2025)
Construction is one of the fastest-growing sectors across the world. Meanwhile, the environmental degradation caused by construction activities has become a concern. Hence, the construction industry requires modern methods and methodologies to fully implement sustainable practices and contribute to achieving sustainable development goals. However, it has faced many obstacles. This study investigates the likely impact of barriers to the integration of BIM technologies into the sustainability assessment of buildings. This study developed a hybrid Delphi-analytic hierarchy process approach to assess the relative importance of barriers to the integration of BIM technologies in building sustainability assessments. A two-round Delphi survey formed the basis for reaching consensus among the expert panel based on a set of 20 essential barriers faced by both the users’ group and the stakeholders’ group, which were derived via content analysis of previous studies. Results of the Delphi survey are used to compute the relative importance of barriers using the analytic hierarchy process. The finding indicates that the users’ group faced three key obstacles: “Shortage of BIM and sustainability experts“, “High staff training costs” and "Resistance to change traditional methods”. The stakeholder’ group encountered three significant challenges: “lack of government policies". “Lack of a legal framework” and “Lack of BIM and sustainability investments”. This study contributes to understanding the obstacles that the construction industry faces when trying to use BIM technologies in the assessment of building sustainability, and it considers the key solutions to overcome these barriers to achieve full integration.